2014
DOI: 10.1021/am502700p
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Self-Assembly of BiVO4–Reduced Graphene Oxide Nanocomposites for Highly Efficient Visible Light Photocatalytic Activities

Abstract: It is commonly considered that the morphology and interface of semiconductor-reduced graphene oxide (rGO) composite photocatalysts play a crucial role in determining their photocatalyzing performance. Herein, we report on the design and synthesis of BiVO4-rGO nanocomposites with efficient interfacial contact by self-assembly of positively charged amorphous BiVO4 powders with negatively charged graphene oxide (GO), followed by a one-step GO reduction and BiVO4 crystallization via hydrothermal treatment. The as-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 60 publications
5
66
0
Order By: Relevance
“…Lin et al demonstrated a novel anion-exchange strategy to prepare BiOI/BiOBr composite which greatly enhanced photocatalytic activity for the degradation of methyl orange (MO) [21]. Wang et al reported an electrostatic self-assembly of BiVO 4 /rGO composite via a simple surface charge method and enhanced photocatalytic activity [22]. Recently, our group successfully prepared a series of titania based photocatalysts by enwrapping heterogeneous semiconductors with titania nanosheets, which exhibited superior photocatalytic performance and stability [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al demonstrated a novel anion-exchange strategy to prepare BiOI/BiOBr composite which greatly enhanced photocatalytic activity for the degradation of methyl orange (MO) [21]. Wang et al reported an electrostatic self-assembly of BiVO 4 /rGO composite via a simple surface charge method and enhanced photocatalytic activity [22]. Recently, our group successfully prepared a series of titania based photocatalysts by enwrapping heterogeneous semiconductors with titania nanosheets, which exhibited superior photocatalytic performance and stability [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…FeWO 4 /graphene composites exhibited high capacity and excellent cyclic stability for both Li-ion and Na-ion batteries, using FeCl 3 ·6H 2 O, and Na 2 WO 4 ·2H 2 O as precursors [13]. Graphene-based composite materials have shown significant improvement in the electronic conductivity and transportation, resulting in good photocatalytic properties [14][15][16][17][18][19][20][21]. However, no literature has reported the photocatalytic properties of FeWO 4 -graphene composites as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…BiVO 4 , with a band gap of 2.4 eV, is an OER catalyst under visible light irradiation because its valence band (VB) is more positive than the H 2 O/O 2 redox potential [8][9][10][11]. And it is also commonly utilized as an excellent visible-light photocatalyst http for pollutant degradation [12][13][14][15]. However, the nature of easy electron-hole recombination in BiVO 4 severely limits its function.…”
Section: Introductionmentioning
confidence: 99%